Surface modification of rare earth nanoparticles for the attachment of drugs. - Stanislaws, Anna Marina. (2011)
Rare earth upconversion nanoparticles (UCNPs) are proving indispensable in various fields of research today ranging from electronic sectors to the biomedical field. In the biomedical field, rare earth UCNPs are explored for their use as fluorescent biomarkers for their use in bioimaging. Traditional down conversion nanophosphors used as luminescent labels exhibit several problems such as low light penetration depth and possible severe photodamage to living organisms. Hence in this project we explore the synthesis of rare earth UCNPs which have a greater advantage over the traditional form as they cause minimal damage to biological tissues and allow deep penetration of NIR radiation. We explore the synthesis of NaYF4:Yb,Er UCNPs surface functionalized with the carboxyl functional group for the attachment of drug through the thermal decomposition, hydrothermal and solvothermal approaches. Their effectiveness to generate NPs which exhibit good surface functionality and solubility for their use in drug delivery into cells when conjugated with Ara-C is then evaluated through FT-IR and TEM imaging. The most efficient strategy can then be adopted to synthesize UCNPs surface-functionalised with other groups to allow greater use in the biomedical field.